Poesia franquista valenciana (1939-1943) - Cortés, Santi; Catalunya, Anna (Caplletra. Revista Internacional de Filologia, 2015)
This paper analyzes the Francoist poetry written in Catalan that was published in Valencia between 1939 and 1943, when the dominant ideology was fascist. A collection of poems appears in the appendix.